(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pertussis is a highly contagious bacterial infection that can be severe, especially in children and immunocompromised individuals. This article examines the epidemiological characteristics, pathogenesis, clinical manifestations, and modern diagnostic methods of the disease. Additionally, the effectiveness of vaccines and immunization programs, as well as the latest scientific approaches to disease prevention, are discussed. Early detection and preventive measures play a crucial role in reducing the spread of the infection.